How Does AI Handle Motion Artifacts in Medical Images? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Motion artifacts are a significant challenge in medical imaging, often leading to degraded image quality, diagnostic inaccuracies, and the need for costly an...
Keywords: AI in Medical Imaging and Diagnostics; Handle; Motion; Artifacts; Artificial Intelligence; Deep Learning; Healthcare